Menstrual dysfunction and body weight dissatisfaction among Finnish young athletes and non-athletes - Ravi, S.; Waller, B.; Valtonen, M.; Villberg, J.; Vasankari, T.; Parkkari, J.; Heinonen, O. J.; Alanko, L.; Savonen, K.; Vanhala, M.; Selänne, H.; Kokko, S.; et al. (Scandinavian Journal of Medicine & Science in Sports, 2021)
To determine the prevalence of menstrual dysfunction (MD; ie, oligomenorrhea or amenorrhea) and attitudes toward body weight among athletes and non-athletes, we studied a cohort of athletes and non-athletes, in adolescence (14-16 years) and subsequently in young adulthood (18-20 years). We further studied the differences between athletes reporting MD and eumenorrheic athletes at both time periods and identified physical and behavioral characteristics that might predict MD in young adulthood. Data were collected using questionnaires, accelerometers, and a pre-participation screening. In adolescence, the athletes reported current primary amenorrhea more often than the non-athletes (4.7% vs 0%, P = .03). In young adulthood, athletes reported MD more frequently than non-athletes (38.7% vs 5.6%, P < .001). Athletes had less desire than non-athletes to lose weight at both time points, and in adolescence, athletes were more satisfied with their weight. However, about one fifth of the athletes and about 40% of the non-athletes experienced body weight dissatisfaction at both time points. In adolescence, athletes reporting MD had lower BMI than eumenorrheic athletes. In young adulthood, athletes with MD were more physically active than eumenorrheic athletes. The only longitudinal predictor of MD in young adulthood was MD in adolescence. Our findings indicate that MD is relatively frequent among young Finnish athletes. However, athletes appear to have a smaller tendency to experience body weight dissatisfaction than their non-athletic peers. MD seems to track from adolescence to adulthood, suggesting that there is a need to focus on possible causes at the earliest feasible phase of an athlete's career.